Լեռնային Ղարաբաղի Հանրապետությունում առաջին անգամ հայտնաբերված ժանգասնկերի համառոտ նկարագիր - Մարգարյան, Գ․
Впервые описаны 44 вида ржавчинных грибов на территории НКР, 24 из которых принадлежат к роду Puccinia, 8- к Phragmidium, 3- к Melampsora, 2- к Gymnosporangium, Aecidium и 1- к Tranzschelia. Определяя виды ржавчинных грибов по особенностям развития, выявилось, что, из представленных 44 видов 33-однохозяйные, а 9 разнохозяйные. Из однохозяйных грибов 16-развиваются неполным, а 17-полным циклом. У 6-ти видов разнохозяйных грибов протекает полный биоцикл, а у 3- неполный. For the first time 44 species of rust fungi on the NKR territory have been examined. Among the revealed species 24- belong to the Puccinia, 8 to Phragmidium, 3 to Melampsora, 2 to Gymnosporangium, Aecidium and 1 to Tranzschelia generas. Determining the types of rust fungi according to the specific characteristics we have revealed that 33 out of 44 species are audacious, 9 are heteroecious. 16 species out of audacious ones develop through the full cycle, 17 through biocycle. 6 heteroecious rust fungis have full biocycle, 3- don't.
Keywords: Սնկաբանություն